Plastome Evolution in Dolomiaea (Asteraceae, Cardueae) Using Phylogenomic and Comparative Analyses - Shen, Jun; Zhang, Xu; Landis, Jacob B.; Zhang, Huajie; Deng, Tao; Sun, Hang; Wang, Hengchang (Frontiers in Plant Science, 2020)
Abstract: Dolomiaea is a medicinally important genus of Asteraceae endemic to alpine habitats of the Qinghai-Tibet Plateau (QTP) and adjacent areas. Despite significant medicinal value, genomic resources of Dolomiaea are still lacking, impeding our understanding of its evolutionary history. Here, we sequenced and annotated plastomes of four Dolomiaea species. All analyzed plastomes share the gene content and structure of most Asteraceae plastomes, indicating the conservation of plastome evolutionary history of Dolomiaea. Eight highly divergent regions (rps16-trnQ, trnC-petN, trnE-rpoB, trnT-trnL-trnF, psbE-petL, ndhF-rpl32-trnL, rps15-ycf1 and ycf1), along with a total of 51-61 simple sequence repeats (SSRs) were identified as valuable molecular markers for further species delimitation and population genetic studies. Phylogenetic analyses confirmed the evolutionary position of Dolomiaea as a clade within the subtribe Saussureinae, while revealing the discordance between the molecular phylogeny and morphological treatment. Our analysis also revealed that the plastid genes, rpoC2 and ycf1, which are rarely used in Asteraceae phylogenetic inference, exhibit great phylogenetic informativeness and promise in further phylogenetic studies of tribe Cardueae. Analysis for signatures of selection identified four genes that contain sites undergoing positive selection (atpA, ndhF, rbcL and ycf4). These genes may play important roles in the adaptation of Dolomiaea to alpine environments. Our study constitutes the first investigation on the sequence and structural variation, phylogenetic utility and positive selection of plastomes of Dolomiaea, which will facilitate further studies of its taxonomy, evolution and conservation. Key words: Dolomiaea; Plastomes; Alpine environments; Phylogenomic framework; Highly divergent regions; Positive selection; Adaptive evolution